2019
DOI: 10.3791/60139
|View full text |Cite
|
Sign up to set email alerts
|

Nest Building Behavior as an Early Indicator of Behavioral Deficits in Mice

Abstract: Nest building is an innate behavior in male and female rodents, even when raised in laboratory settings. As such, many researchers provide rodents synthetic and/or natural materials (such as twine, tissue, cotton, paper, and hay) as a gauge of their overall well-being and as an ancillary assessment to predict the possible decline in cognition. Typically, changes in nesting behaviors, such as failure to create a nest, indicate a change in health or welfare. In addition, nesting behavior is sensitive to many env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…Mice would remove large portions of bedding from the burrow and start dispersing it in a thin layer in concentric circles on the surface of the corncob bedding. This behavior appears opposite to nest building behavior where soft substrate is accumulated (Deacon, 2012;Neely et al, 2019).…”
Section: Discussionmentioning
confidence: 85%
“…Mice would remove large portions of bedding from the burrow and start dispersing it in a thin layer in concentric circles on the surface of the corncob bedding. This behavior appears opposite to nest building behavior where soft substrate is accumulated (Deacon, 2012;Neely et al, 2019).…”
Section: Discussionmentioning
confidence: 85%
“…Estep et al (1975) [ 83 ] used unbleached cotton batting, Torres-Lista & Giménez-Llort (2013) [ 77 ] compared paper towel and cotton, while Xiong et al (2018) [ 82 ] used white paper (similar to the current experiment). Neely et al (2019) [ 50 ] has shown that the type of material used to evaluate nesting can give different responses by raters that are blind to experimental condition, with higher average nest scores being given to mice using shredded paper (as done here and in previous research [ 57 , 79 ]) as compared to cotton squares, bedding, and paper twists. Shredded paper has also been shown to lead to more consistent results [ 50 ].…”
Section: Discussionmentioning
confidence: 87%
“…Neely et al (2019) [ 50 ] has shown that the type of material used to evaluate nesting can give different responses by raters that are blind to experimental condition, with higher average nest scores being given to mice using shredded paper (as done here and in previous research [ 57 , 79 ]) as compared to cotton squares, bedding, and paper twists. Shredded paper has also been shown to lead to more consistent results [ 50 ].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations